The long-term outcomes of antiretroviral treatment initiated with mono or dual nucleoside reverse transcriptase inhibitors in HIV-1-infected children: an Asian observational study - Orasri Wittawatmongkol; Thahira J. Mohamed; Thoa P.K. Le; Vibol Ung; Alan Maleesatharn; R.awiwan Hansudewechakul; Lam V. Nguyen; Nagalingeswaran Kumarasamy; Pagakrong Lumbiganon; Tavitiya Sudjaritruk; Torsak Bunupuradah; Nik K.N. Yusoff; et al. (Elsevier, 2015)
After a median of 115.9 months of follow-up, 90% of 206 HIV-1-infected children in a cohort in Asia who initiated antiretroviral treatment (ART) with mono or dual nucleoside reverse transcriptase inhibitors were alive and had comparable immunological and virological outcomes as compared to the 1,915 children who had started with highly active antiretroviral regimens. However, these children had higher rates of treatment-related adverse events, opportunistic infections, and cumulative mortality, and were more likely to require protease inhibitor-containing regimens or other more novel ART-based regimens.